2017
DOI: 10.1101/136580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Evolution of Small-RNA-Mediated Silencing of an Invading Transposable Element

Abstract: Transposable elements (TEs) are genomic parasites that impose fitness costs on their hosts by producing deleterious mutations and disrupting gametogenesis. Host genomes avoid these costs by regulating TE activity, particularly in germline cells where new insertions are heritable and TEs are exceptionally active. However, the capacity of different TE-associated fitness costs to select for repression in the host, and the role of selection in the evolution of TE regulation more generally, remain controversial. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 98 publications
3
27
1
Order By: Relevance
“…If individuals with large clusters end up with fewer deleterious TE insertions than individuals with small clusters, large clusters may be positively selected. This hypothesis is supported by recent simulation studies which found that TE insertions within piRNA clusters may be positively selected (Lu and Clark, 2009;Kofler, 2019;Kelleher et al, 2018). Large clusters will on the average end up with more TE insertions than small cluster.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…If individuals with large clusters end up with fewer deleterious TE insertions than individuals with small clusters, large clusters may be positively selected. This hypothesis is supported by recent simulation studies which found that TE insertions within piRNA clusters may be positively selected (Lu and Clark, 2009;Kofler, 2019;Kelleher et al, 2018). Large clusters will on the average end up with more TE insertions than small cluster.…”
Section: Discussionmentioning
confidence: 52%
“…Fifth, piRNA cluster are mostly composed of TE sequences (Brennecke et al, 2007), supporting the view that clusters carry the trapped remnants of past TE invasions. Sixth, computer simulations confirm that genomic traps, such as piRNA clusters, may stop TE invasions (Kofler, 2019;Kelleher et al, 2018;Lu and Clark, 2009).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Most importantly, however, high-quality assemblies will allow us to study the evolution of piRNA clusters. We could, for example, test the hypothesis that the composition of piRNA clusters evolves rapidly, as expected under the widely held trap model (Kelleher et al, 2018;Kofler, 2019). Long-read based assemblies may thus revolutionize TE research.…”
Section: Introductionmentioning
confidence: 94%